2018
DOI: 10.1186/s12935-018-0649-1
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of LASS2 inhibits proliferation and causes G0/G1 cell cycle arrest in papillary thyroid cancer

Abstract: BackgroundThe aim of this study was to investigate the role of LAG1 longevity-assurance homologue 2 (LASS2) in papillary thyroid cancer (PTC).MethodsImmunohistochemistry staining was conducted to explore the expression levels of LASS2 in PTC tissues and adjacent normal thyroid tissues and nodular goiter tissues. Western blotting and RT-qPCR were performed to explore the expression levels of LASS2 in three PTC cell lines (TPC-1, K1, BCPAP). An Adv-LASS2-GFP recombinant adenovirus vector was constructed and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Western blotting analysis was performed as previously described 26. The primary antibodies against the following proteins used in the experiment were from commercial sources: anti-JAZF1 (ab80329; 1:200) and anti-p65 (ab16502; 1:2000), both purchased from Abcam; anti-Bcl-2 (#15071; 1:500) and anti-p-p65, both purchased from CST; anti-Bax (ET1603-34; 1:2000) purchased from Hangzhou HuaAn Biotechnology Co., Ltd.; anti-TAK1 (12330-2-AP; 1:500) purchased from Proteintech; anti-GAPDH (SC-365062; 1:800) purchased from Santa Cruz Biotechnology, Inc. (Dallas, TX, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting analysis was performed as previously described 26. The primary antibodies against the following proteins used in the experiment were from commercial sources: anti-JAZF1 (ab80329; 1:200) and anti-p65 (ab16502; 1:2000), both purchased from Abcam; anti-Bcl-2 (#15071; 1:500) and anti-p-p65, both purchased from CST; anti-Bax (ET1603-34; 1:2000) purchased from Hangzhou HuaAn Biotechnology Co., Ltd.; anti-TAK1 (12330-2-AP; 1:500) purchased from Proteintech; anti-GAPDH (SC-365062; 1:800) purchased from Santa Cruz Biotechnology, Inc. (Dallas, TX, USA).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that proliferation can be enhanced by knocking out Cers2 after sciatic nerve injury (20). Cers2, which is known as a cell proliferation inhibitor, may participate in G0/G1 cell cycle arrest as previous studies (21,22) described. The cell cycle arrest may via a p53-dependent pathway (23).…”
Section: Discussionmentioning
confidence: 77%
“…However, the cell proliferation and invasive ability decreased and the cell apoptosis increased upon the overexpression of the variants compared with the control, especially the T3 variant. which may be interpreted that the TLC domain of TMSG-1/LASS2, a characteristic domain of LASS family involved in the synthesis of ceramide, contributed partially to suppressing cell proliferation, invasive ability and promoting cell apoptosis [6, 19,20].…”
Section: Discussionmentioning
confidence: 99%